USE OF E-OFFICE AS A MEDIA FOR MANAGING EMPLOYEE DATA AT PT KERETA API INDONESIA (PERSERO) OPERATIONAL AREA 7 MADIUN - Fatim Hanenda Putri, Queena; Azis, Aminudin (Politeknik Negeri Madiun, 2025)
Global competition in the world of work is getting tighter, every company must have a strategy to be able to win the competition, one of which is by opening a branch office. However, with the existence of branch offices that are located differently from the head office, it makes it difficult to submit employee data management reports to the head office. Currently, many companies use office automation technology. The office automation strategy carried out by PT KAI (Persero) DAOP 7 Madiun is through the implementation of e-office. This study aims to determine the e-office work system used as a medium for managing employee data at PT KAI (Persero) DAOP 7 Madiun. The research method used is descriptive qualitative with data collection techniques in the form of interviews and documentation. The results of the study indicate that the e-office work system at PT KAI (Persero) DAOP 7 Madiun is used in managing employee data including input, process, storage, output and distribution. Input data in e-office contains data about the company and employees. The data processing process carried out is in the form of data manipulation and image editing. Data is stored using storage in the form of a database on a data storage server. After the data is saved, the output produced is in the form of hard copy and soft copy, then the data is distributed to each e-office user account.